Analysis of BUMDes Readiness in Implementing a Digital Accounting Information System and Its Implications for the Quality of Financial Reports - Ajeng Puspita Savitri; Mahmud Mahmud; Rizky Ramadhan (Economics and Digital Business Review, 2026)
This study aims to explore in-depth the readiness of the Village-Owned Enterprise (BUMDes) of Nusa Jaya in implementing a Digital Accounting Information System (AIS) and its implications for the quality of financial reports. The research method used is a qualitative approach with a case study design. Data validity was tested using triangulation techniques, while data analysis applied the Miles and Huberman interactive model. The results highlight that the readiness level of the BUMDes is still at an early initiation stage and has not fully implemented digital AIS. Financial operations are still managed using Microsoft Excel due to limitations in technological infrastructure, human resource (HR) competence, and budget support. Interestingly, despite not being fully digitalized, the quality of the resulting financial reports still meets the aspects of relevance, completeness, timeliness, and transparency. This achievement is supported by effective manual internal control mechanisms through a definitive division of tasks, password protection, dual data storage, and physical archiving. It is concluded that the current reporting quality is built on managerial commitment rather than technological sophistication. To optimize future accuracy, efficiency, and data integration, improving HR competencies and providing technological infrastructure are absolutely necessary to support comprehensive digital transformation.